2004
DOI: 10.1021/ma0356358
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Responsive Water-Soluble Polymers Based on 2-Hydroxyethyl Methacrylate

Abstract: The homopolymerization and block/statistical copolymerization of 2-hydroxyethyl methacrylate (HEMA) using atom transfer radical polymerization (ATRP) in methanol at 20 °C has been investigated. For the homopolymerizations, both high conversions and low polydispersities (M w/M n < 1.25) were obtained over a wide range of target degrees of polymerization. According to the literature, HEMA homopolymer is usually described as only water-swellable, but in this work low molecular weight HEMA oligomers (target degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
307
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(333 citation statements)
references
References 38 publications
15
307
2
Order By: Relevance
“…ature solubility (Figure 3a), similar to lower molecular weight PHEMA (cloud point temperatures ∼28-39°C in dilute aqueous solutions at pH 6.5 18 ) and PEG homopolymers. 23 For PEG, this interesting behavior has been explained in terms of entropic effects of fitting PEO molecules into the water network, 24 conformationdependent hydrophobicity, 25 and competititive etherwater and water-water H-bonding.…”
Section: Figurementioning
confidence: 70%
“…ature solubility (Figure 3a), similar to lower molecular weight PHEMA (cloud point temperatures ∼28-39°C in dilute aqueous solutions at pH 6.5 18 ) and PEG homopolymers. 23 For PEG, this interesting behavior has been explained in terms of entropic effects of fitting PEO molecules into the water network, 24 conformationdependent hydrophobicity, 25 and competititive etherwater and water-water H-bonding.…”
Section: Figurementioning
confidence: 70%
“…On the other hand, the water solubility of the resulting polymer is well known to crucially depend on the molecular weight of PHEMA. [270][271] As the described microgels were prepared by free radical copolymerization, no control over the molecular weight of PHEMA was achieved. As a consequence, the resulting lengths of the polymeric chains of the gel network were assumed to be in the range of restricted water solubility and thus hindering particles swelling in aqueous medium.…”
Section: Photo-sensitive Phema Microgels: Light-triggered Swellingmentioning
confidence: 99%
“…As for PEO-b-PHEMA copolymer, although PEO and PHEMA are water soluble blocks, HEMA homopolymers with DPn"s higher than 50 were actually partially soluble [20]. So PEO-b-PHEMA-4 was selected to investigate its self-assembly in water.…”
Section: Self-assembly Of Peo-b-phema Copolymer In Watermentioning
confidence: 99%
“…A recent overview on the synthetic routes toward DHBCs and some of their prominent applications was presented by Colfen [1]. Armes [20] found that copolymerizations of HEMA with other comonomers allowed the cloud point behavior to be manipulated. A range of novel HEMA-based block copolymers were synthesized in which the HEMA block was either thermo-responsive or permanently hydrophilic, depending on its degree of polymerization (DP n ) and the nature of the second block.…”
Section: Introductionmentioning
confidence: 99%